Does elective orthopaedic surgery in the pandemic era increase the risk of developing COVID-19? A combined analysis of retrospective and prospective study at a national tertiary hospital in Jakarta, Indonesia (2020)
Background: To date, no recommendations have been published on when and how to start again carrying out elective, non-urgent surgery on COVID-19-negative patients after the epidemic peak has been reached in a given country or region and the pressure on healthcare facilities, healthcare workers and resources has been released by so far that elective surgery procedures can be safely and ethically programmed again. This study aims to investigate whether elective orthopaedic surgery will increase the risk of developing COVID-19. Materials and Methods: This was a combined retrospective and prospective studies performed at a national tertiary hospital in Jakarta, Indonesia. Subjects were patients who underwent elective orthopaedic surgeries at our institution from April to May 2020. Those who were previously infected with COVID-19 from polymerase chain reaction (PCR) reverse transcriptase (RT) examination obtained via nasopharynx and oropharynx swab, as well as those who were reluctant to participate were excluded from the study. Results: A total of 35 subjects (mean age 32.89 ± 17.42) were recruited. Fifteen (42.9%) subjects were male, and 20 subjects (57.1%) were female. Mean duration of surgery was 240 minutes with the longest and shortest duration of 690 and 40 minutes, respectively. General anaesthesia was performed in the majority of cases in 18 surgeries (51.4%) with local anaesthesia as the least in 2 surgeries (5.7%). Length of stay of our study was 6 days of average. None of the patients developed symptoms suggestive of COVID-19 infection. Conclusion: We found that elective orthopaedic surgery may not be associated with increased cases of COVID-19 cases. However, our study was limited by short duration of follow-up. Further studies are required in order to investigate the affect of undergoing elective surgery and the number of COVID-19 cases.